Resting-State Functional MRI Metrics in Patients With Chronic Mild Traumatic Brain Injury and Their Association With Clinical Cognitive Performance - Vedaei, Faezeh; Newberg, Andrew B.; Alizadeh, Mahdi; Muller, Jennifer; Shahrampour, Shiva; Middleton, Devon; Zabrecky, George; Wintering, Nancy; Bazzan, Anthony J.; Monti, Daniel A.; Mohamed, Feroze B. (Frontiers in Human Neuroscience, 2021)
Mild traumatic brain injury (mTBI), or concussion accounts for more than 80% of people experiencing brain injury along with deficits in cognitive performance, executive functioning, and working memory that persist months and years post injury. In this study, we conducted resting-state functional magnetic resonance imaging (rs-fMRI) to measure voxel-based indexes named fractional amplitude of low frequency fluctuation (fALFF), regional homogeneity (ReHo), and functional connectivity (FC) in patients suffering from chronic mTBI. 64 patients with chronic mTBI at least three months post injury, and 40 healthy controls underwent rs-fMRI scanning. Furthermore, partial correlation analysis controlling for age and gender was performed within mTBI cohort to examine the association between rs-fMRI metrics and neuropsychological scores. Compared to controls, patients showed increased fALFF in the left middle occipital cortex (MOC), right middle temporal cortex (MTC), and right angular gyrus (AG), as well as increased ReHo in the left MOC and left posterior cingulate cortex (PCC). Enhanced FC from left MOC to right precuneus, from right MTC to right superior temporal cortex (STC), right supramarginal, and left inferior parietal cortex (IPC) as well as from the seed located at right AG to left precuneus, left superior medial frontal cortex (SMFC), left MTC, left superior temporal cortex (STC), and left MOC were revealed. Regarding cognitive performance, the findings provided evidence of correlation between clinical scores and fALFF, ReHo extracted from the regions with significant differences between two groups, as well as seed-based FC. Our results demonstrated alteration of low-frequency oscillations in chronic mTBI that could be representative of disruption in emotional circuits, cognitive performance, and recovery in this cohort.